On the Construction of Multipolar Intuitionistic Fuzzy Positive Implicative Ideals in BCK-Algebras - Dian Nan Brylliant; Syafitri Hidayahningrum; Wahyuningsih; Wafiq Sulistiawati R. Syarif Maulana (Bincang Sains dan Teknologi, 2026)
This research focuses on the generalization of the concept of multipolar fuzzy intuitionistic ideal in BCK algebra and bi-polar fuzzy intuitionistic positive implicative ideal in BCK algebra into multipolar fuzzy intuitionistic positive implicative ideal in BCK algebra. In this research, we define the concept of multipolar fuzzy intuitionistic positive implicative ideal in BCK algebra, and given the examples. In addition, we examine the conditions that must be met by a multipolar fuzzy intuitionistic ideal in BCK algebra to become a multipolar fuzzy intuitionistic positive implicative ideal in BCK algebra. One of the theorems produced in this research is that a multipolar intuitionistic fuzzy (P ̂,Q ̂) of X is a multipolar intuitionistic fuzzy implicative ideal (P ̂,Q ̂) of X if and only if (P ̂,Q ̂) is a multipolar intuitionistic fuzzy ideal of X and P ̂(x*y)≥P ̂((x*y)*y) and Q ̂(x*y)≤Q ̂((x*y)*y) apply, for all x,y,z∈X, where X is a BCK algebra.